Mange mite infestation of rabbit in Meghalaya - RAJKHOWA, C; BANDYOPADHYAY, S; GOSWAMI, S N (The Indian Journal of Animal Sciences, 2013)
Ear cankar and skin lesion caused by Psoroptes cuniculi and Sarcoptes scabiei respectively, were identified from rabbit farm in Meghalaya. There was single infestation of Psoroptes cuniculi and Sarcoptes scabiei but mixed infestation bf both the species was also detected. P. cuniculi infestation ranged from 2.47% in June to 8.00% in January. S. scabiei infestation ranged from 3.24% in May to 8.14% in October, while mixed infestation ranged from 1.08% in April to 3.90% in December. A temperature range of 13.94o-+01: 5.04°C to 24.58°-+3.14°C was the most vulnerable range for higher incidence. Animals below 3 months of age were not found infested. In P. cuniculi apart from crust fonnation, yellowish brown exudate rich, in mite content was found oozing out. In P. cuniculi infestation clinical sign of torticollis. was noticed in a few cases.